Study on the Histological Changes in the Parenchyma of the Placentae of Preeclamptic Women (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
Context: The histological changes in internal components of the placenta are evident in different maternal diseases like preeclampsia. Postnatal examination of the placenta is an important method for assessing pathophysiological changes as well as maternal and fetal condition in antenatal and perinatal periods and enriching practical knowledge. Study design: Cross-sectional, descriptive type. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from August 2005 to June 2006. Materials & Methods: 60 human placentae from Bangladeshi women were collected from the Department of Obstetrics & Gynaecology of Dhaka Medical College Hospital, Dhaka and Sir Salimullah Medical College Hospital, Dhaka, of which 30 from normal uncomplicated pregnancies (control group) and another 30 from pregnancies complicated by preeclampsia (study group), where the patients were normotensive previously. Results: A reduction in the proportional volume peripheral villi and an increase in that of stem villi were found in the placentae of the preeclamptic women (P0.50). Moreover, there was an increased fibrinoid deposition in the placentae of the preeclamptic women (P